GSDMD (Gasdermin D) Mediates Pathological Cardiac Hypertrophy and Generates a Feed-Forward Amplification Cascade via Mitochondria-STING (Stimulator of Interferon Genes) Axis. Issue 11 (6th September 2022) - Han, Jibo; Dai, Shanshan; Zhong, Lingfeng; Shi, Xiaowen; Fan, Xiaoxi; Zhong, Xin; Lin, Wante; Su, Lan; Lin, Shuang; Han, Bingjiang; Xu, Jianjiang; Hong, Xia; et al.
Abstract : Background: Cardiac hypertrophy is initially an adaptive response of cardiomyocytes to neurohumoral or hemodynamic stimuli. Evidence indicates that Ang II (angiotensin II) or pressure overload causes GSDMD (gasdermin D) activation in cardiomyocytes and myocardial tissues. However, the direct impact of GSDMD on cardiac hypertrophy and its underlying mechanisms are not fully understood. Methods and Results: In this study, we examined the aberrant activation of GSDMD in mouse and human hypertrophic myocardia, and the results showed that GSDMD deficiency reduced Ang II or pressure overload–induced cardiac hypertrophy, dysfunction, and associated cardiomyocyte pyroptosis in mice. Mechanistically, Ang II–mediated GSDMD cleavage caused mitochondrial dysfunction upstream of STING (stimulator of interferon genes) activation in vivo and in vitro. Activation of STING, in turn, potentiated GSDMD-mediated cardiac hypertrophy. Moreover, deficiency of both GSDMD and STING suppressed cardiac hypertrophy in cardiac-specific GSDMD-overexpressing mice. Conclusions: Based on these findings, we propose a mechanism by which GSDMD generates a self-amplifying, positive feed-forward loop with the mitochondria-STING axis. This finding points to the prospects of GSDMD as a key therapeutic target for hypertrophy-associated heart diseases.